2020
DOI: 10.1002/chem.202001127
|View full text |Cite
|
Sign up to set email alerts
|

Soft Scorpionate Hydridotris(2‐mercapto‐1‐methylimidazolyl) borate) Tungsten‐Oxido and ‐Sulfido Complexes as Acetylene Hydratase Models

Abstract: As eries of W IV alkyne complexes with the sulfurrich ligand hydridotris(2-mercapto-1-methylimidazolyl) borate)(Tm Me)a re presented as bio-inspired modelst oe lucidate the mechanism of the tungstoenzyme acetylene hydratase (AH). The mono-a nd/or bis-alkyne precursors were reacted with NaTm Me and the resulting complexes [W(CO)(C 2 R 2)(Tm Me)Br] (R = H 1,M e2)o xidizedt ot he target [WE(C 2 R 2)(Tm Me)Br] (E = O, R = H 4,M e5;E= S, R = H 6,M e7) using pyridine-N-oxidea nd methylthiirane. Halide abstraction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…IR spectra show one strong band indicative of ν(W=O) at 924 cm –1 . 14 , 26 28 The 1 H NMR spectrum of 3 in CD 2 Cl 2 shows two equally sharp singlets flanked with 183 W satellites for the C 2 H 2 protons at 11.23 and 10.99 ppm. Thus, they are shifted upfield compared to 1 .…”
mentioning
confidence: 99%
“…IR spectra show one strong band indicative of ν(W=O) at 924 cm –1 . 14 , 26 28 The 1 H NMR spectrum of 3 in CD 2 Cl 2 shows two equally sharp singlets flanked with 183 W satellites for the C 2 H 2 protons at 11.23 and 10.99 ppm. Thus, they are shifted upfield compared to 1 .…”
mentioning
confidence: 99%
“…Values for the stretching frequency of the metalÀ oxygen bond are in accordance with the literature and do not vary significantly among themselves (914-927 cm À 1 ). [19,30,45] NMR spectra recorded in CD 2 Cl 2 show again the presence of only one isomer for the C 2 Me 2 and C 2 Ph 2 complexes 6a, 6b, 8a, and 8b, while two isomers with respect to the orientation of the coordinated HC 2 Ph are observed of both 7a and 7b. In 1 H-NMR spectra of 6a and 6b, the protons of the two C 2 Me 2 methyl groups appear as broad quadruplets, and hence they couple with each other with J = 1.0 Hz, while no coupling of the C 2 Me 2 protons is observed in the respective carbonyl complexes 1a and 1b.…”
Section: Synthesis Of Oxido Complexesmentioning
confidence: 88%
“…[29,30] Due to the strong trans effect of the oxido ligand, the opposite metalÀ sulfur bond (2.6218(6) -2.6690(5) Å) is considerably longer than the other (2.4097(6) -2.4194(6) Å) in all presented complexes as already observed in [MoO (PMe 3 )(6-MePyS) 2 ]. [53] While W(IV) oxido C 2 R 2 complexes are already quite established, [19,21,45,54] the structures of complexes 6b, 7b, and 8b represent the first examples of Mo(IV) oxido C 2 R 2 complexes.…”
Section: Synthesis Of Oxido Complexesmentioning
confidence: 99%
“…The first tungsten­(II) acetylene species bearing dithiocarbamate ligands was reported in 1978; thereafter, only a few other W–C 2 H 2 adducts have been synthesized. For example, Templeton et al reported a tungsten­(IV) oxo acetylene complex containing an N-donor boron-based scorpionate ligand . In our group, the use of bioinspired S,N-bidentate ligands, such as SPhoz (2-(4′4′-dimethyloxazoline-2′-yl)­thiophenolate), PyS (pyridine-2-thiolate), and 6-MePyS (6-methylpyridine-2-thiolate), allows the preparation of W­(II) and W­(IV) complexes and ensures a sulfur-rich environment, more closely resembling the one in the native enzyme.…”
Section: Introductionmentioning
confidence: 99%